Analisis Pengendalian Internal Sistem Penggajian CV. Usaha Jaya dengan Pendekatan COSO ERM 2013 - Purnamasari, Rachma Dewanti; Rahmat, Kamaluddin (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study analyzes the implementation of internal control in the payroll system of CV. Usaha Jaya to address salary payment delays caused by lengthy verification processes, non-integrated systems, and limited human resources. The objective is to evaluate the effectiveness of internal control using the COSO ERM (2013) framework and to identify improvements to enhance the efficiency and accuracy of payroll. The method used is descriptive qualitative, with data collected through semi-structured interviews, observations, and document studies. The results show that the internal control design meets most COSO ERM components, such as organizational structure, authorization procedures, and documentation; however, its implementation is still suboptimal due to weak segregation of duties, manual attendance and payroll systems, and the absence of formal risk management procedures. The study concludes that an integrated payroll information system, clearer segregation of functions, and formal risk-handling procedures are needed to improve the effectiveness, efficiency, and transparency of the payroll process.